3D Numerical study on the flow topology and heat transfer characteristics of turbulent forced convection in spirally corrugated tube. (18th March 2016) - Promthaisong, P.; Jedsadaratanachai, W.; Eiamsa-ard, S.
ABSTRACT: This paper presents a numerical analysis on flow configurations and heat transfer characteristics of turbulent forced convection in spirally corrugated tubes. The influences of corrugation depth (DR = 0.02–0.16), pitch ratio (PR = 0.10–1.00), and Reynolds number (Re = 5, 000–20, 000) on flow structure and heat transfer characteristics are described. Comparisons between the full length and periodic domains are also reported. The results show that spirally corrugated tubes induced vortex flows which helped to increase heat transfer due to enhanced fluid mixing. The maximum thermal enhancement factor of 1.16 was obtained by using the spirally corrugated tube with DR = 0.06, PR = 0.25 at Re = 5, 000.